Interpersonal Trauma and Sexual Function and Satisfaction: The Mediating Role of Negative Affect Among Survivors of Military Sexual Trauma - K. Blais, Rebecca (Journal of interpersonal violence, 2022)
Healthy sexual function among women service members/veterans (SM/Vs) is associated with higher quality of life, lower incidence and severity of mental health diagnoses, higher relationship satisfaction, and less frequent suicidal ideation. Although trauma exposure has been established as a predictor of poor sexual function and satisfaction in women SM/Vs, no study to date has examined whether specific trauma types, such as military sexual trauma (MST), increase risk for sexual issues. Moreover, the possible mechanisms of this association have not been explored. The current study examined whether posttraumatic stress disorder (PTSD) and depression symptom clusters mediated the association of trauma type and sexual function and satisfaction in 426 trauma-exposed women SM/Vs. Two hundred seventy participants (63.4%) identified MST as their index trauma. Path analyses demonstrated that MST was related to poorer sexual function and lower satisfaction relative to the other traumas (?2[28, N = 426] = 43.3, p = 0.03, CFI = 1.00, TLI = 0.99, and RMSEA = 0.04), and this association was mediated by higher non-somatic depressive symptoms and PTSD symptom clusters of anhedonia and negative alterations in cognition and mood (NACM). Causality cannot be inferred due to the cross-sectional nature of the data. However, our findings suggest that interventions aimed at decreasing sexual issues among female SM/Vs with MST should target depressogenic symptoms, whether the origin is depression or PTSD. Longitudinal research exploring the etiological processes that contribute to sexual dysfunction among those with MST is needed.